Adaptability of the Immature Ocular Motor Control System: Unilateral IGF-1 Medial Rectus Treatment - Willoughby, Christy L. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. Unilateral treatment with sustained release IGF-1 to one medial rectus muscle in infant monkeys was performed to test the hypothesis that strabismus would develop as a result of changes in extraocular muscles during the critical period of development of binocularity. METHODS. Sustained release IGF-1 pellets were implanted unilaterally on one medial rectus muscle in normal infant monkeys during the first 2 weeks of life. Eye position was monitored using standard photographic methods. After 3 months of treatment, myofiber and neuromuscular size, myosin composition, and innervation density were quantified in all rectus muscles and compared to those in age-matched controls. RESULTS. Sustained unilateral IGF-1 treatments resulted in strabismus for all treated subjects; 3 of the 4 subjects had a clinically significant strabismus of more than 10°. Both the treated medial rectus and the untreated ipsilateral antagonist lateral rectus muscles had significantly larger myofibers. No adaptation in myofiber size occurred in the contralateral functionally yoked lateral rectus or in myosin composition, neuromuscular junction size, or nerve density. CONCLUSIONS. Sustained unilateral IGF-1 treatment to extraocular muscles during the sensitive period of development of orthotropic eye alignment and binocularity was sufficient to disturb ocular motor development, resulting in strabismus in infant monkeys. This could be due to altering fusion of gaze during the early sensitive period. Serial measurements of eye alignment suggested the IGF-1-treated infants received insufficient coordinated binocular experience, preventing the establishment of normal eye alignment. Our results uniquely suggest that abnormal signaling by the extraocular muscles may be a cause of strabismus.